Gen Z and the Digital Marketplace: A Quantitative Analysis of Age and Gender Differences in Online Shopping Behaviors and Payment Preferences in Nepal - Chaudhary, Satyanarayan; Deo, Manju Kumari (Nepal Journal of Multidisciplinary Research, 2025)
Background: The Nepalese online commerce market is undergoing a drastic transformation with the penetration of e-commerce sites and mobile wallets. Identifying what drives the market requires a closer examination of its most dynamic segment: Generation Z. This study investigates the payment behavior and buying habits online of this generation with special interest in examining the impact of age and gender. Objectives: The primary aims were to: 1) trace the frequency, platform, and product preference of Nepali Gen Z for online purchases, 2) assess their adoption and attitude towards mobile wallets, and 3) empirically test for age and gender differences. Methods: Quantitative cross-sectional design was employed. Pre-coded survey was conducted online and a sample of 216 Gen Z respondents (20-25 years) was received. Data was analyzed using SPSS, Independent Samples t-tests for examining gender differences and Pearson Correlation and Chi-Square tests for examining the effect of age. Results: Analysis of the data showed a widespread lack of statistically significant gender variations in online buying frequency, product selection, and problem experience. However, age appeared in a substantive, weak correlation with attitudes towards payment. In addition, choice of platform had a complex, non-linear relationship with age, showing nuanced intra-generational trends. Conclusion: The research concludes that in the case of Generation Z in Nepal, gender is not a fundamental differentiator of overall online shopping behavior, but age remains a salient factor influencing payment and platform choice. This demonstrates a homogenizing effect of digital nativity on gender-based consumption routines. Implication: The findings indicate that platform developers and marketers should be concerned with age and lifestyle segmentation rather than focusing on gender-based solutions for the Gen Z generation. Solution efforts have to be aimed at simplifying payment solutions and platform functionality to cater to the subtle, age-differentiated inclinations of this key audience.